PERENCANAAN DAERAH TUJUAN WISATA (TINJAUAN: PERENCANAAN KAWASAN TAMAN PURBAKALA NASIONAL BOROBUDUR) - Teguh Hadi Sukarno (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2019)
This is an overviews the planning of The Temple Borobudur as a Tourism Destination. Idially, there are at least three parties involved in planning a tourism area namely : Government, Tourism Industries and local community with their interests. Tourism Destination has to meet some criteria to be successful. Aspect of organizational and marketing planning, product aspect and the aspects of quality planning. Tourism development initiated with good planning is expected to give beneficial impact to the local industry, government and community. A good tourism planning will take into consideration in the very beginning all the possible impacts, positive or negative so that all measures can be planned in advance to anticipate them. The Desk Research/Secondary Research is using to analyse the article